Interspecific comparisons of lymph volume and lymphatic fluxes: Do lymph reserves and lymph mobilization capacities vary in anurans from different environments? - Hillman, S.; Drewes, R.; Hedrick, M.; Withers, Philip (The University of Chicago Press, 2011)
The femoral lymph sac volumes and lymph mobilization capacity were compared in three anuran species that span a range of environments, dehydration tolerance, ability to maintain blood volume with dehydration, and degrees of development of skeletal muscles putatively involved in moving lymph vertically to the posterior lymph hearts. The femoral lymph sac volume determined by Evans blue injection and dilution in the femoral lymph sac varied interspecifically. The semiaquatic species, Lithobates catesbeianus, had the greatest apparent lymph volume expressed either as 18.7 mL kg body mass-1 or 94 mL kg thigh mass-1, compared with both the terrestrial and aquatic species, Rhinella marina (7.3 mL kg body mass-1 and 57 mL kg thigh mass-1) and Xenopus laevis (6.5 mL kg body mass-1 and 40 mL kg thigh mass-1), respectively. Injections of Evans blue into the subvertebral lymph sac, which communicates with both pairs of lymph hearts, yielded the highest rates of lymph return to the circulation in all three species. The most terrestrial species had a greater rate of lymphatic return from the subvertebral lymph sac, compared with the other two species. The rate of lymph flux from the femoral sac varied interspecifically and was correlated with the number and development of skeletal muscles involved in lymph movement. The results indicated that the three species differ in both the volume of lymph present and the capacity to return lymph. Lymph flux was correlated with habitat and the ability to maintain blood volume when challenged by dehydration or hemorrhage, whereas femoral lymph volume was not correlated with these factors. © 2011 by The University of Chicago.